Quantification and Mechanistic Investigation of the Spontaneous H2O2 Generation at the Interfaces of Salt-Containing Aqueous Droplets - Angelaki, Maria; Carreira Mendes Da Silva, Yoan; Perrier, Sébastien; George, Christian (Journal of the American Chemical Society, 2024)
There is now much evidence that OH radicals and H2O2 are spontaneously generated at the air–water interface of atmospheric aerosols. Here, we investigated the effect of halide anions (Cl–, Br–, I–), which are abundant in marine aerosols, on this H2O2 production. Droplets were generated via nebulization of water solutions containing Na2SO4, NaCl, NaBr, and NaI containing solutions, and H2O2 was monitored as a function of the salt concentration under atmospheric relevant conditions. The interfacial OH radical formation was also investigated by adding terephthalic acid (TA) to our salt solutions, and the product of its reaction with OH, hydroxy terephthalic acid (TAOH), was monitored. Finally, a mechanistic investigation was performed to examine the reactions participating in H2O2 production, and their respective contributions were quantified. Our results showed that only Br– contributes to the interfacial H2O2 formation, promoting the production by acting as an electron donor, while Na2SO4 and NaCl stabilized the droplets by only reducing their evaporation. TAOH was observed in the collected droplets and, for the first time, directly in the particle phase by means of online fluorescence spectroscopy, confirming the interfacial OH production. A mechanistic study suggests that H2O2 is formed by both OH and HO2 self-recombination, as well as HO2 reaction with H atoms. This work is expected to enhance our understanding of interfacial processes and assess their impact on climate, air quality, and health.